2014
DOI: 10.1039/c4ob00187g
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission enhancement upon Al3+ complexation with a tetrasulfonated calix[4]bisazacrown fluorescent molecular sensor

Abstract: Aggregation-induced emission and aggregation-induced emission enhancement have attracted much attention due to their great potential in real-world applications. Up to now most of the reports are based on the restriction of free rotation of the luminogens in the aggregates. In the present work, we found that the dansyl fluorophore with typical intramolecular charge transfer characteristic also exhibited aggregation-induced emission enhancement, which was based on the change of micro-environmental polarity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The relationship manifested that Ni‐MOG possessed high sensitivity to detect low Al 3+ ion concentration. Based on 3 σ / k , where σ is the standard deviation of the blank and k is the slope of the linear fitting, the limit of detection for Al 3+ ion was calculated to be 0.5 μM, which is much lower than meeting the requirement of WHO with a limit of 7.41 μM Al 3+ in drinking water …”
Section: Resultsmentioning
confidence: 99%
“…The relationship manifested that Ni‐MOG possessed high sensitivity to detect low Al 3+ ion concentration. Based on 3 σ / k , where σ is the standard deviation of the blank and k is the slope of the linear fitting, the limit of detection for Al 3+ ion was calculated to be 0.5 μM, which is much lower than meeting the requirement of WHO with a limit of 7.41 μM Al 3+ in drinking water …”
Section: Resultsmentioning
confidence: 99%
“…However, the decay time of derivative 5 in 50% water fraction (0.30 ns) is longer than that of 5 in 0% water fraction (0.081 ns) which implies formation of ordered aggregates. 39 We also carried out the uorescence anisotropy studies [40][41][42] of derivative 7 which show an increase in the average anisotropy value of derivative 7 in DMSO from 0.05 to 0.32 in H 2 O-DMSO (1 : 1, v/v) (Fig. S14 and S15 in ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…40 Recent work has also shown that aggregation-induced emission can result in enhancement of dansyl fluorescence, however this is accompanied by a significant shift in emission wavelength. 41 Analogous titration with bromide, nitrate and acetate resulted in similar enhancement, with a shoulder appearing to lower wavelength in the case of acetate.…”
Section: Dansylamide Derived Calixarenesmentioning
confidence: 92%